Ferromagnetic, dielectric, and ferroelectric characteristic near the morphotropic phase boundary in (1-x)(0.7BiFeO3-0.3BiNa0.5Ti O3)-x(CaTiO3) solid solution. Issue 14 (15th July 2021) - Chakrabarti, Chiranjib; Fu, Qingshan; Paul, Biplab Kumar; Chen, Xinghan; Zheng, Jia; Yin, Hongxia; Ali, Wajahat; Qiu, Yang; Roy, Pradip Kumar; Suthar, Mukesh; Yuan, Songliu
Abstract: The substitution of CaTiO3 in 0.7BiFeO3 -0.3Ba0.5 Na0.5 TiO3 solid solutions unveil some fascinating structural, ferromagnetic, dielectric, ferroelectric and resistive response. A comprehensive phase structural investigation confirms that the solid solutions experience a structural shift from the Rhombohedral R3c phase to the Tetragonal P4bm phase accompanied by the development of an intermediate phase boundary (MPB) within a particular composition range (0.05 = x ≤ 0.15). Besides, a subsidiary orthorhombic ( Pbnm ) phase of the substituent CaTiO3 emerges for x ≥ 0.1, which eloquently affects the magnetic properties of the solid solutions. A well-organized dielectric, ferroelectric, and activation energy analysis demonstrate that CaTiO3 substitution can spectacularly modulate the dielectric and resistive properties within the MPB range, successively suppressing the space charge effects. Furthermore, an impedance spectroscopic analysis advocates that grain boundary facilitated space charge conduction exists in the solid solutions.